Vasily Ilmenev “Explanatory Dictionary” - Alla M. Gracheva (Studia Litterarum)
This publication introduces a hitherto unknown text by Alexey Remizov, previously not included in bibliographic references. Remizov’s “Explanatory Dictionary,” published under the pseudonym “Vasily Ilmenev” is a review of the first volume of the Explanatory Dictionary of the Russian Language edited by D.N. Ushakov (Moscow, 1935). The attribution and analysis of the “Explanatory Dictionary” have allowed me to qualify it as a work with artistic value that may be thematically and stylistically included in a series of Remizov’s prose miniatures in the two volumes of Remizov’s book Russia in Letters. As his sources, Remizov used a number of dictionary articles that recorded and explained words that were relevant in the USSR before 1937 (“to brand,” “to slander,” “denunciation,” etc.). The inclusion of the miniature “Explanatory Dictionary” in the writer’s legacy better understanding of the writer’s attitude to the Stalin regime. It is an unusual work for Remizov as it openly expresses the author’s political views.